Triglyceride-glucose index and overactive bladder syndrome: evidence from the NHANES 2005-2018 - Chen, Baitong; Wang, Jiongming; Huang, Yueting; Chen, Nanhui (Frontiers in Endocrinology, 2025)
IntroductionThe relationship between the triglyceride-glucose index (TyG) and overactive bladder (OAB) is unclear. The aim of this study was to investigate the possible association between the TyG index and OAB.MethodsNational Health and Nutrition Examination Survey (NHANES) data from 2005–2018 were used. The association between TyG index and OAB was assessed using univariate and multivariate logistic regression models. In addition, restricted cubic spline curves were used to examine the dose-response relationship between TyG index and OAB risk. Subgroup analyses and interaction analyses were then performed to assess differences in associations between subgroups.ResultsA total of 14,059 participants with 3325 patients with OAB were included. In the fully adjusted model, each unit increase in the TyG index was associated with a 1.18-fold increased risk of OAB (OR = 1.18; 95% CI: 1.11-1.26; p < 0.001) and a 1.32-fold increased risk of OAB for Q4 compared to Q1 at the quartile level (OR = 1.32, 95% CI: 1.17- 1.50, p < 0.001), RCS analysis showed a positive linear association between TyG index and OAB, and subgroup analysis showed that the association between TyG and OAB was more pronounced in individuals younger than 60 years and in women (p for interaction < 0.05).ConclusionThe results of this study suggest that TyG index is positively associated with OAB, and this association was more pronounced in younger age groups and in females.TyG index, as a simple and cost-effective metabolic marker, may provide a potential tool for early screening of OAB, especially in individuals with metabolic abnormalities that have not progressed to significant metabolic diseases.